Economic evaluation of intravenous iron treatments in the management of anemia patients in Greece - Fragoulakis V; Kourlaba G; Goumenos D; Konstantoulakis M; Maniadakis N (Dove Medical Press, 2012)
Vassilis Fragoulakis1, Georgia Kourlaba1, Dimitris Goumenos2, Manousos Konstantoulakis3, Nikolaos Maniadakis11Department of Health Services Management, National School of Public Health, Athens, 2Department of Medicine University Hospital of Patras, Patras, 3Department of Medicine, Athens Medical School, Athens, GreecePurpose: To conduct an economic evaluation comparing Ferinject® (ferric carboxymaltose [FCM]) with Venofer® (iron sucrose [IS]) and CosmoFer® (low-molecular-weight iron dextran [LMWID]) in the management of iron deficiency anemia in Greece.Patients and methods: A cost-minimization analysis was conducted since there are no clear data indicating that one of these regimens is superior to the others in terms of efficacy. Main data inputs were based on bibliography and validated by clinicians. The economic evaluation was conducted for inpatients (ie, surgical patients or patients hospitalized due to a disease related to chronic or acute blood loss) and outpatients (eg, nondialysis chronic kidney disease patients), separately. Analysis was carried out from a National Health Service (NHS) perspective and also from a patient perspective. Total cost treatment reflects the cost of drugs, the cost of all resources expended in patient management such as the cost of disposables for each infusion, the monitoring costs during infusion (salaries of personnel), other hospital expenses, the cost for management of adverse events, the productivity loss, and the traveling cost for patients.Results: In the case of outpatients, the mean total cost per patient in the FCM arm was €198.6, in the IS arm €627.7, and in the LMWID arm, €510.5. For inpatients the mean total cost was estimated at €189.2 for FCM while it was €419.9 and €228.8 for IS and LMWID, respectively. Budget impact analysis for a typical Greek hospital with 100 patients revealed that the total cost of FCM (inpatients analysis) was 113% and 15.4% lower against their comparators. In an outpatient situation, the total cost of FCM was 201.1% and 151.8% lower compared with IS and LMWID, respectively.Conclusion: Ferric carboxymaltose may represent a cost-saving option compared with the most likely alternative existing therapies used for the management of anemia in the National Health Service of Greece.Keywords: economic evaluation, cost minimization, ferric carboxymaltose, anemia, iron therapy